Intercultural Mediation as a strategy to facilitate relations between the School and Immigrant Families - Catarci, Marco (Revista Electrónica Interuniversitaria de Formación del Profesorado, 2016)
The contribution focuses on the role of intercultural mediator as a facilitator of relationships between the school and immigrant families. The perspective of interculturalism in schools represents the political and educational response to the challenges of the multicultural society. In this task, strategies of intercultural mediation have been adopted in the schools in order to develop links and promote effective relationships between people from different cultures. In particular, an intercultural mediator (also called a ‘community interpreter’ or a ‘cultural linguistic’ or ‘cross-cultural mediator’ in certain contexts) is an operator in charge of facilitating communication between individuals, families, and community as part of measures to promote and facilitate the social inclusion of immigrants. As a mediator between immigrants and the society of reception, he/she promotes the removal of cultural and language barriers, the development of a culture of openness, inclusion and the advocacy of rights, and observance of the duties of citizenship. Moreover he/she facilitates the expression of immigrants’ needs on the one hand, and the characteristics, resources, and constraints of the welfare system on the other. Finally some key results of quantitative research in Italy are presented with regard to biographical and professional experience of intercultural mediators active in the Italian school system.